Can Belief in God be Basic? - Matteo, Anthony M. (Horizons, 1988)
At least since the Enlightenment, religious thinkers in the West have sought to meet the "evidentialist" challenge, that is, to demonstrate that there is sufficient evidence to warrant a rational affirmation of the existence of God. Alvin Plantinga holds that this challenge is rooted in a foundationalist approach to epistemology which is now intellectually bankrupt. He argues that the current critique of foundationalism clears the way for a fruitful reappropriation of the Reformed (Calvinist) tradition's assertion of the "basic" nature of belief in God and its concomitant relegation of the arguments of natural theology to marginal status. After critically assessing Plantinga's proposal—especially its dependence on a nonfoundationalist theory of knowledge—this essay shifts to an analysis of the transcendental Thomist understanding of the rational underpinnings of the theist's affirmation of God's existence, with particular emphasis on the thought of Joseph Maréchal. It is argued that the latter position is better equipped to fend off possible nontheistic counterarguments—even in our current nonfoundationalist atmosphere—and, in fact, can serve as a necessary complement to Calvin's claim of a natural tendency in human beings to believe in God.